Characterizing Lipid‐Coated Mesoporous Silica Nanoparticles as CD169‐Binding Delivery System for Rilpivirine and Cabotegravir. Issue 5 (13th March 2022) - Zang, Han; Fofana, Josiane; Xu, Fangda; Nodder, Sarah B.; Gummuluru, Suryaram; Reinhard, Björn M.
Abstract : Herein, lipid‐coated mesoporous silica nanoparticles (LMSNs) are investigated as biomimetic delivery vehicle for two antiretroviral (ARV) compounds, rilpivirine (RPV), and cabotegravir (CAB). Monosialodihexosylganglioside (GM3) is incorporated into the membrane to facilitate LMSN binding to CD169 (Siglec‐1)‐expressing myeloid cells, that are predominantly expressed in secondary lymphoid tissues in vivo. It is demonstrated that in addition to providing CD169‐binding functionalities, the lipid membrane around the silica core provides stealth properties that dampen the inflammatory cytokine response to ARVs‐loaded LMSN in human monocyte‐derived macrophages. Quantification of RPV and CAB releases from nanoparticles, and assessment of antiviral potency to human immunodeficiency virus 1 (HIV‐1) infection in vitro reveals that RPV and CAB co‐formulated into LMSN retain optimal antiviral potency for 90 days, even upon storage at room temperature, making LMSN an attractive nanoplatform, immune to cold chain requirements. These findings suggest that GM3–LMSN equip the mesoporous silica nanoparticle (MSN) core with lipid‐derived properties for surface passivation and lipid‐mediated binding that are of high interest for achieving an effective delivery of ARVs to tissue reservoirs of HIV‐1 replication. Abstract : Herein, ganglioside‐incorporated lipid‐coated mesoporous silica nanoparticles (LMSN) are investigated as biomimetic delivery vehicle for two antiretrovirals: rilpivirine and cabotegravir. Lipid coating provides CD169‐binding functionality, stealth property, and altered drug release kinetics. Co‐loading of rilpivirine and cabotegravir into LMSN yields synergistic HIV‐1 inhibition in vitro, making LMSN a potential platform for delivering antiretrovirals to tissue reservoirs of HIV‐1 replication.